A new near-infrared ratiometric fluorescent probe for hydrazine. Issue 41 (12th May 2017) - He, Yangyang; Li, Zhanxian; Shi, Bingjie; An, Zhen; Yu, Mingming; Wei, Liuhe; Ni, Zhonghai
Abstract : Under mild conditions, a novel near-infrared ratiometric and on–off fluorescent probe was synthesized, which can detect hydrazine with high selectivity and anti-interference over other amines, biological species, anions and metal ions. Abstract : It is important to develop fluorescent probes for rapid, selective, and sensitive detection of highly toxic hydrazine in both environmental and biological science. In this text, under mild conditions, a novel near-infrared (NIR) ratiometric and on–off fluorescent probe1 was synthesized based on hemicyanine and coumarin derivatives, which can detect hydrazine with high selectivity and anti-interference over other amines, biological species, anions and metal ions. The limit of quantification (LOQ) value was 0–400 μM and the detection limit could be as low as 560 nM.